microRNAs responsive to A. actinomycetemcomitans and P. gingivalis LPS modulate expression of genes regulating innate immunity in human macrophages - Naqvi, Afsar R. (2013)
microRNAs (miRNA) are a class of small noncoding RNAs that regulate post-transcriptional expression of their respective target genes and are responsive to various stimuli, including lipopolysaccharide (LPS). Here we examined the early (4h) miRNA responses of THP1-differentiated macrophages challenged with LPS derived from the periodontal pathogens, Aggregatibacter actinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg) or environmentally modified LPS obtained from Pg grown in cigarette smoke extract. Predicted miRNA-gene target interactions for LPS-responsive miR-29b and let-7f were confirmed using dual-luciferase assays and by transfection experiments using miRNA mimics and inhibitors. Convergent and divergent miRNA profiles were observed in treated samples where differences in miRNA levels related to the type, concentration and incubation times of LPS challenge. Dual-luciferase experiments revealed miR-29b targeting of IL-6Rα and IFN-γ inducible protein 30 (IFI30) and let-7f targeting of suppressor of cytokine signaling 4 (SOCS4) and Thrombospondin-1 (TSP-1). Transfection experiments confirmed miR-29b and let-7f modulation of IL-6R and SOCS4 protein expression levels, respectively. Thus, we demonstrate convergent/divergent miRNA responses to wild type and its environmentally-modified LPS and demonstrate miRNA targeting of key genes linked to inflammation and immunity. Our data indicate that these LPS-responsive miRNAs may play a key role in fine-tuning the host response to periodontal pathogens.